THE INFLUENCE OF ANTECEDENTS OF BRAND EQUITY ON THE FAST FOOD INDUSTRY. - Afifah Wulandari; Fatik Rahayu (Jurnal Ekonomi Trisakti, 2023)
This study aims to analyze the effect of Brand Awareness, Perceived Quality and Brand Association on Brand Equity in the Fast Food Industry. The method used is non-probability sampling using purposive sampling technique. Sampling was done by distributing questionnaires to 200 respondents. Respondents in this study are consumers who use beauty products and active social media users. Hypothesis testing was carried out using the Structural Equiation Model (SEM) with the help of AMOS24. The results showed that Brand Awareness, Perceived Quality and Brand Association had a positive effect on Brand Equity.